Backbone Reactivity of Lithium β‐Diketiminate (NacNac) Complexes with CO2, tBuNCO and iPrNCO. Issue 64 (18th October 2019) - Gauld, Richard M.; McLellan, Ross; Kennedy, Alan R.; Barker, Jim; Reid, Jacqueline; Mulvey, Robert E.
Abstract: Though alkali metal NacNac (β‐diketiminate) complexes have been utilised in synthesis as NacNac‐transfer agents, studies of them in their own right with small molecules are exceptionally rare. Here, the lithium compound of the common 2, 6‐diisopropylphenyl‐β‐methyldiketiminate [NacNac(Dipp, Me)] ligand is investigated with carbon dioxide and isocyanates. In all four cases reaction occurs at the backbone γ‐C atom of the NacNac ligand, which redistributes electronically into a diimine. Insertion of CO2 gives an eight‐atom carboxylate (Li2 O4 C2 ) ring at the γ‐C site in a dimer. Insertion of t BuNCO gives a secondary amide at the γ‐C site in a monomer with TMEDA chelating lithium. Double insertion of t BuNCO and (adventitious) oxygen gives a dimer with a (LiO)2 central core involving the latter source. Insertion of less bulky ( i PrNCO) gives a dimer with dimerisation through the C=O bonds of the emergent secondary amide function. Abstract : The knack of NacNac backbone functionalisation : Reaction of the lithium NacNac(Dipp, Me) complex with carbon dioxide and isocyanates affords a series of structurally diverse products, with insertion of the small molecules at the γ‐C site of the NacNac ligand, which rearranges into a diimine formulation.